Metastatic Thymic Carcinoma on Restaging 18F-Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography - Hoe Khoo, Alex Cheen (Indian J Nucl Med, 2020)
Thymic carcinoma is a rare thymic epithelial cancer which is not only locally invasive but also highly aggressive disease. The prognosis for this cancer is poor and the surgery remains the mainstay of treatment. Thymic carcinomas have been shown to metastasize to the lymph nodes, lung, and liver. A 63-year old male who was successfully treated for thymic cancer in 2015, presented with metastatic disease recurrence to the spinal cord. We share interesting images of the spinal cord lesions as well as pituitary metastases that were incidentally detected on restaging 18F-fluorodeoxyglucose positron emission tomography-computed tomography.